Universal density shift coefficients for the thermal conductivity and shear viscosity of a unitary Fermi gas - Xiang Li; J. Huang; J. E. Thomas (Physical Review Research)
We measure universal temperature-independent density shifts for the thermal conductivity κ_{T} and shear viscosity η, relative to the high temperature limits, for a normal phase unitary Fermi gas confined in a box potential. We show that a time-dependent kinetic theory model enables extraction of the hydrodynamic transport times τ_{η} and τ_{κ} from the time-dependent free decay of a spatially periodic density perturbation, yielding the static transport properties and density shifts, corrected for finite relaxation times.